Study of Sports Translation from the Perspective of Functional Equivalence - Mao, Junsen (International Journal of Social Sciences and Public Administration, 2024)
With people’s continuous pursuit of a better life, sports has been thriving in the whole world, becoming an important way for people to enhance their physical fitness and improve their health. Secondly, in the frequent communication and collision of world civilizations, sports has been a good way to alleviate cultural conflicts. However, sports spread cross the international communication, involving language transition and translation. In the translation practice, the orientations of value and the choices of strategy for sports are playing significant role in the further development of sports in globe. Yet there only are a few sports translation researches currently, so the research of translation strategy, method, orientation, paradigm, evaluation framework is still has a huge blank that need us to fill . This paper focuses on the translation of sports terms, on the basis of Nida’s functional theory of equivalence, tries to establish a benign understanding bridge between the target-text readers and the original-text readers, improve the consistency of their acceptance effect, and promote the development of sports and cultural communication.